SOCIAL ENVIRONMENTAL CONFLICTS IN THE BASIN STREAM OF FERN, DISTRITO FEDERAL ”“ BRASIL - Goulart, Nilton; Anjos, Rafael Sanzio Araújo dos (Revista Eletrônica: Tempo - Técnica - Território / Eletronic Magazine: Time - Technique - Territory, 2016)
The environmental thematic subject can also be seen under the optics of the conflict, since the natural resources are be objects of disputes and interests. The subjects of the environment can be classified according to types different from conflict and they elapse of the dispute or misunderstanding related with the exploration of the natural resources, tending to increase with the shortage and competition for the natural resource. In the end of the century 20 the conflicts related with environment began to be studied under that environmental vision.